Applying Dataflow Architecture and Visualization Tools to In Vitro Pharmacology Data Automation. (December 2016) - Pechter, David; Xu, Serena; Kurtz, Marc; Williams, Steven; Sonatore, Lisa; Villafania, Artjohn; Agrawal, Sony
The pace and complexity of modern drug discovery places ever-increasing demands on scientists for data analysis and interpretation. Data flow programming and modern visualization tools address these demands directly. Three different requirements—one for allosteric modulator analysis, one for a specialized clotting analysis, and one for enzyme global progress curve analysis—are reviewed, and their execution in a combined data flow/visualization environment is outlined.